Representation of globalization on Youtube video “Wonderland Indonesia” - adinda putri, Adinda Putri Surya Kencana; filosa gita, Filosa Gita Sukmono (Universitas Ahmad Dahlan, 2022)
Globalization occurs in tandem with the development of technology to become more sophisticated. The development of globalization can have an impact on every line of people's lives, one of which is culture, so that its spread can also be through the internet, one of which is through YouTube videos. This study aims to see how globalization is represented by Alffy Rev through his work entitled